Effectiveness of treatment of occipital neuralgia using the nerve block technique: a prospective analysis of 44 patients - Juškys, Raimondas; Šustickas, Gytis (Acta medica Lituanica, 2018)
Background. There is a great deal of tools for treatment of occipital neuralgia but currently we are lacking a complete consensus among practitioners regarding the optimal approach to this debilitating condition. Occipital nerve block (ONB) is known as one of the management options but there is lack of scientific literature exploring its effectiveness. Materials and methods. The prospective study was undertaken between March 2014 and February 2018 at the State Vilnius University Hospital. Fortyfour patients aged from 28 to 84 years (age mean = 56.30 ± 14.71) of which 79.55% were female (n = 35) were diagnosed with occipital neuralgia (ON) and treated with a local anaesthetic and corticosteroids combination injection into the greater or greater plus lesser occipital nerve (n = 29 and n = 15, respectively) and followed up after 6 months. Analysis of the outcomes of those patients was done by comparing the Visual Analog Scale (VAS) and Barrow Neurological Institute Pain Intensity Score (BNIPIS) prior to treatment, 24 hours after the block, and at a follow-up 6 months later. Analgesic medication consumption before and after 6 months was recorded. A comparison of procedure efficacy in lidocaine and bupivacaine groups was made. Evaluation of block potency for acute and chronic pain categories was conducted as well. The success criteria were defined as patient satisfaction with own condition for at least 6 months, not requiring another block in order to stay comfortable. Results. Of 44 patients, 42 (95.45%) who underwent the occipital nerve block procedure showed satisfactory results for at least 6 months. Mean headache VAS scores decreased from 7.23 ± 0.93 (pre-treatment) to 1.95 ± 1.59 (24 hours after, p < 0.0001) and increased to 2.21 ± 1.73 at the follow-up after 6 months, showing no statistically significant difference between post-interventional and six-month VAS scores (p = 0.07). In all patients the necessity of medication to control pain decreased to 16.67% (n = 7) during the the check-up after 6 months. There was no statistically significant difference in the effectiveness of ONB with regard to the local anaesthetic used or the pain group targeted. Similar results were obtained comparing patients who underwent more than one ONB. Conclusions. Occipital nerve block with a local anaesthetic and corticosteroids provides a safe, simple, and effective treatment method for the patient with medically-refractory occipital neuralgia.